Importance of controlling mesocotyl elongation in the development of rice seedlings intended for mechanical transplantation - Jia, Yuanli; Wang, Tao; Zhou, Gaozi; Tang, Lei; Yue, Xueping; Liu, Xinrui; Cao, Tao; Yang, Juan; Tao, Youfeng; Deng, Fei; Zhou, Wei; Ren, Wanjun; et al. (Frontiers in Plant Science, 2023)
The mesocotyl facilities the emergence of deep-sown rice. However, the effects of mesocotyl elongation on mechanically transplanted rice seedlings remain unclear. In this study, the indica three-line hybrid rice Chuanyou 6709 (CY6709) and the indica conventional rice Guichao II (GCII) were selected as experimental materials. The seedlings were grouped based on mesocotyl lengths of 1.0 and 2.0 cm (M1 and M2, respectively), and seedlings without mesocotyl elongation were used as a control (M0). Seedling morphology, root morphology and physiology, and dynamic changes in soluble sugar and protein, malondialdehyde (MDA), and antioxidant enzyme activity in the mesocotyl were evaluated. The results showed that the elongation of mesocotyl is not conducive to improving the quality of mechanically transplanted seedlings, resulting in weak seedlings and poor root coiling force. The mesocotyl lengths of the seedlings showed a single peak with increasing seedling age, which gradually disappeared. The longer the mesocotyls, the slower their senescence. The MDA content of M2 was significantly lower than that of M1, and the activities of soluble sugar, soluble protein, and antioxidant enzymes of M2 were higher than those of M1, implying that seedlings with longer mesocotyls yielded lower-quality seedlings, reducing their suitability for mechanized transplantation. Compared with those of M0, the root-shoot ratio, stem base width, leaf age, leaf area, white root number, root coiling force, root length, root surface area, and root volume of M1 and M2 were reduced. Therefore, in the raising of rice seedlings, excessive elongation of the rice mesocotyl is not conducive to optimum root growth and development of aboveground structures for seedlings that are suitable for mechanized transplantation. Controlling the mesocotyl elongation can facilitate the cultivation of high-quality mechanically transplanted seedlings.